EFFECTS OF FEEDING FEED ENRICHED CURCUMIN TURMERIC (Curcuma domestica Val) OVERVIEW OF THE RED BLOOD CELLSPangasius hypophthalmus - Malau, Diana P; Riauwaty, Morina; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in June-August 2016. The purpose of this study was todetermine the effect of feeding feed enriched curcumin turmeric (Curcuma domestica Val)to the picture of the red blood cells (total erythrocytes, hematocrit, and hemoglobinconcentration) Pangasiushypophthalmus and infected by Aeromonas hydrophilla. Thedesign used was Completely Randomized Design (CRD) with one factor, the level 5treatments and 3 replications. The treatments were feeding enriched curcuminextract withdifferent dose i.e Kn = negative control (feeding without being given curcumin extract andwere not infected byAeromonashydrophilla); Kp = positive control (feeding without beinggiven curcumin extract and infected byAeromonashydrophilla); P1 = addition of curcuminextract in feed at a dose of 0.3 g/kg; P2 = addition of curcumin extract in feed at a dose of0.5 g/kg; and P3 = addition of curcumin extract in feed at a dose of 0.7 g/kg. The resultsshowed that feeding enriched curcuminextract against of Pangasiushypophthalmus at adose of 0.7 g/kg (P3) is the best dose for Pangasiushypophthalmuswith a total oferythrocyte 1.87x106 cells/mm3, hematocrit 35.33 %, and hemoglobin concentration of 7.66g/dl after infected byAeromonashydrophilla and generate growth in absolute weight of 3.66g and a survival rate of 100 %.Keywords:Curcuminextract, Pangasius hypophthalmus, Aeromonas hydrophila, Totalerythrocytes,